2017
DOI: 10.1038/nplants.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Growing the lost crops of eastern North America's original agricultural system

Abstract: Thousands of years before the maize-based agriculture practiced by many Native American societies in eastern North America at the time of contact with Europeans, there existed a unique crop system only known through archaeological evidence. There are no written or oral records of how these lost crops were cultivated, but several domesticated subspecies have been identified in the archaeological record. Growth experiments and observations of living progenitors of these crops can provide insights into the ancien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Of the six species of eastern Northern American domesticates, only squash (Curcubita pepo) and sunflower (Helianthus annus) are currently still grown as crops (Smith, 2006;Smith and Yarnell, 2009). However, there is revived interest in many of the eastern Northern American domesticates (Mueller et al, 2017), as well as similarly developed species in Europe, Latin America, Africa, Asia, and Oceania (Dirzo and Raven, 2003;Smykal et al, 2018). For example, a recent review by Smykal and colleagues recommends several lost African species that could be recultivated (Council, 1996;Henry et al, 2016;Smykal et al, 2018).…”
Section: Redomesticationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the six species of eastern Northern American domesticates, only squash (Curcubita pepo) and sunflower (Helianthus annus) are currently still grown as crops (Smith, 2006;Smith and Yarnell, 2009). However, there is revived interest in many of the eastern Northern American domesticates (Mueller et al, 2017), as well as similarly developed species in Europe, Latin America, Africa, Asia, and Oceania (Dirzo and Raven, 2003;Smykal et al, 2018). For example, a recent review by Smykal and colleagues recommends several lost African species that could be recultivated (Council, 1996;Henry et al, 2016;Smykal et al, 2018).…”
Section: Redomesticationmentioning
confidence: 99%
“…For example, a recent review by Smykal and colleagues recommends several lost African species that could be recultivated (Council, 1996;Henry et al, 2016;Smykal et al, 2018). Furthermore, experiments have demonstrated that goosefoot cultivation can already produce harvests comparable with those of agricultural crops (Herná ndez Bermejo and Leó n, 1994; Patton and Williams, 2016), suggesting that redomestication of this species via selective breeding or gene editing could render it an attractive alternative to the exotic species currently grown in North America (Mueller et al, 2017).…”
Section: Redomesticationmentioning
confidence: 99%
“…Thirty crop species supply over 90% of the world’s food needs and this narrow diversity reduces global food security. Humans have domesticated several hundred distinct plant species, but most are underutilized, under-improved, and restricted to their regions of origin 1 . Although food systems have become increasingly diverse in the last few decades, many locally adapted species have been replaced by calorically dense staple crops, resulting in global homogeneity 2 .…”
Section: Introductionmentioning
confidence: 99%
“…T hirty crop species supply over 90% of the world's food needs and this narrow diversity reduces global food security. Humans have domesticated several hundred distinct plant species, but most are underutilized, under-improved, and restricted to their regions of origin 1 . Although food systems have become increasingly diverse in the past few decades, many locally adapted species have been replaced by calorically dense staple crops, resulting in global homogeneity 2 .…”
mentioning
confidence: 99%